The Role of Organizational Climate Mediation InServant Leadership Relations with Employee Job Satisfaction and Organizational Commitment at Polda Aceh (International Journal of Scientific Research and Management (IJSRM), 2024)
This study aims to determine the mediating role of organizational climate in the relationship of servant leadership on job satisfaction and organizational commitment of the Aceh Regional Police officers. Because all the populations of this study were identified, the sample design used in this study was probability sampling by using the approach of stratified random sampling. Data were collected from 258 Aceh Police officers, which were then processed using Structural Equation Modeling (SEM). The results showed that Servant Leadership affects Job Satisfaction, Organizational Commitment, and Organizational Climate; Organizational climate affects job satisfaction but does not affect Organizational Commitment; Organizational Climate mediates the Servant Leadership effect on Job Satisfaction partially, and mediates Servant Leadership effect on Organizational Commitment fully. These findings also reveal that the model of increasing job satisfaction and organizational commitment in Aceh Regional Police employees is a function of increasing Servant Leadership and the suitability of the organizational climate. This model can be a basis for conducting research related to existing variables